STUDI PENGARUH VARIASI SUHU KALSINASI TERHADAP KEKERASAN BENTUK MORFOLOGI, DAN ANALISIS POROSITAS NANOKOMPOSIT CAO/SiO2 UNTUK APLIKASI BAHAN BIOMATERIAL - Akhmad Kurniawan; Muchammad Nizar; Muhammad Rijal; Redy Bagas; Woro Setyarsih (Universitas Negeri Surabaya, 2014)
Biomaterial substance is needed by citizen, but the suplayed is limited and expansive. It become inspirations give new efisience inovations biomaterial subtance from nature. For that research is done which has purpose to make biomaterial subtance from eggsheld waste and mud. Method which is used are nanocomposite CaO/SiO2 syntesis and mix by ratio 2:1., than calcinations by temperature 700oC, 800oC, 900oC, than caracterize use hardness vickers, SEM, BET test. The result of caracteritation of show that at 900oC the quality highest hardness receand is 109,1 ± 5,22 VHN. Than microstructure where in this temperature granula which clod and became bigger the pore little. Where as for its porositation analyzed at this temperature of surface value is 23.843 m2/g and pore volume is 0.007 cc/g. From the analysis can get conclutions that the increasing by temperature of calcinations coused hardness quality increase and influence microstructure also surface area at the sample surface.